2015
DOI: 10.15252/embj.201490880
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomeric p53 binding prevents accumulation of DNA damage at human telomeres

Abstract: Telomeres and tumor suppressor protein TP53 (p53) function in genome protection, but a direct role of p53 at telomeres has not yet been described. Here, we have identified non-canonical p53-binding sites within the human subtelomeres that suppress the accumulation of DNA damage at telomeric repeat DNA. These non-canonical subtelomeric p53-binding sites conferred transcription enhancer-like functions that include an increase in local histone H3K9 and H3K27 acetylation and stimulation of subtelomeric transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 59 publications
2
57
0
Order By: Relevance
“…These fusions were most abundant in the TP53 −/− samples, in line with their raised inter-chromosomal fusion frequencies (Supplemental Fig. 1C) and further evidencing the significant genomic instability resulting from the loss of this mitotic checkpoint and subtelomeric protection (Tutton et al 2015). The absence of functional LIG3 or LIG4 did not significantly reduce the incidence of 17p intra-chromosomal fusion events detected, and importantly, the intra-chromosomal fusion frequency in the LIG3…”
Section: Intra-chromosomal Fusions Exhibit Asymmetrical Processingsupporting
confidence: 61%
“…These fusions were most abundant in the TP53 −/− samples, in line with their raised inter-chromosomal fusion frequencies (Supplemental Fig. 1C) and further evidencing the significant genomic instability resulting from the loss of this mitotic checkpoint and subtelomeric protection (Tutton et al 2015). The absence of functional LIG3 or LIG4 did not significantly reduce the incidence of 17p intra-chromosomal fusion events detected, and importantly, the intra-chromosomal fusion frequency in the LIG3…”
Section: Intra-chromosomal Fusions Exhibit Asymmetrical Processingsupporting
confidence: 61%
“…Genome-wide studies show that p53 binds to many loci in the genome, including sites not associated with transcriptional control [75]. Recently, the prevention of accumulation of DNA damage by p53 binding to subtelomeric regions has been described [76]. Walter et al showed that p53 induces local distortions in mismatched trinucleotide repeats and suggested that p53 may be involved in the maintenance of CTG.CAG tract stability [12, 30, 33].…”
Section: Discussionmentioning
confidence: 99%
“…29 Numerous studies showed that telomere dysfunction induces changes in cellular TERRA levels. 10,30,31 Depletion of TRF2 resulted in up-regulation of TERRA.…”
Section: Cfterra Biogenesismentioning
confidence: 99%